DAKWAH KOLABORATIF DALAM SOSIALISASI SYARIAT ISLAM DI KOTA LANGSA - M. Sufi Abdul Muthalib (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2016)
The problem question of Sharia in Aceh has been hampered by weak quality of dissemination to the public. Socialization during this partially done without involving many parties, while in the same time syaria has many complex issues that needs a holistic endeavor. Collaboratif dawah become an alternative way to maximize the achievement of the Islamic Sharia goal itself.